EFFECT OF PHYSICIAN FACE MASK USE ON POSTINJECTION ENDOPHTHALMITIS. Issue 11 (November 2022) - Fortes, Blake H.; Astafurov, Konstantin V.; Hodge, David O.; Smith, Wendy M.; Barkmeier, Andrew J.; Olsen, Timothy W.; Iezzi, Raymond; Bakri, Sophie J.
Abstract : This multicenter retrospective, comparative cohort study found that physician face mask use did not affect the rate or visual outcome of postinjection endophthalmitis. However, there was a significant reduction in infectious endophthalmitis at MCR after physician face mask implementation that led to a low rate of postinjection endophthalmitis. Abstract : Purpose: To examine the impact of physician face mask use on the rates and outcomes of postinjection endophthalmitis. Methods: A multicenter retrospective, comparative cohort study comparing endophthalmitis rate and visual acuity of eyes that developed endophthalmitis after antivascular endothelial growth factor injections at Mayo Clinic Rochester (MCR) and at Mayo Clinic Health System sites depending on physician masking. Results: A total of 164, 824 injections were performed at MCR and Mayo Clinic Health System sites. Of these, 66, 098 injections were in the no mask group and 98, 726 injections were in the mask group. Overall, there were no differences in the rates of infectious endophthalmitis in the no mask versus mask cohorts (overall: no mask: 20 cases [0.0303%] vs. mask: 41 cases (0.0415%); P = 0.24; infectious: no mask: 12 cases [0.018%] versus mask: 13 cases [0.0132%]; P = 0.42). At MCR alone, there was a significant reduction in infectious endophthalmitis between the no mask versus mask groups (no mask: 9 cases [0.0297%] versus mask: 2 cases [0.003%]; P < 0.001). Only 2 cases of infectious endophthalmitis occurred at MCR after the face mask policy was implemented (1 in 30, 000 injections). At presentation and at 6 months, the average visual acuity was similar for patients who developed endophthalmitis between the no mask versus mask groups. Conclusion: Physician face mask use did not affect the rate or outcome of postinjection endophthalmitis. However, there was a significant reduction at MCR after masking along with other quality improvement measures, including performance of injections in a dedicated procedure room and preparation of patients by nurses, that led to a low rate of endophthalmitis.